Baicalein improves insulin resistance via regulating SOCS3 and enhances the effect of acarbose on diabetes prevention. (October 2017) - Sun, Wenlong; Sun, Jin; Zhang, Bowei; Xing, Yan; Yu, Xiaoxia; Li, Xia; Xiu, Zhilong; Dong, Yuesheng
Highlights: Baicalein from S. baicalensis and O. indicum is used as food supplements in Asia. Baicalein improves insulin resistance by regulating SOCS3 in vitro and in vivo . Moderate baicalein consumption reduces the side-effects of acarbose. Baicalein improves the effect of acarbose on diabetes prevention. Abstract: Baicalein, a major component in Scutellaria baicalensis and Oroxylum indicum, is used as dietary supplement in Asia. In this study, we characterized the insulin-sensitizing activity of baicalein and found that baicalein improved insulin resistance by reducing the expression of SOCS3, increasing the phosphorylation of IRS1 and Akt1, reducing the phosphorylation of GSK3β and increasing hepatic glycogen level. We further evaluated the preventive effect of baicalein combined with acarbose in mice, aiming to enhance the therapeutic effect and reduce the side-effects of acarbose. The combination reduced the relative risk of progression from prediabetes to diabetes by 83.3% and the dose of acarbose by 80%. The underlying mechanisms include reducing postprandial hyperglycemia, improving insulin resistance, improving lipid metabolism, and reducing oxidative stress. Our results suggest that the consumption of 195–780 mg/d baicalein might improve the efficacy of acarbose on diabetes prevention and reduce the side-effects of acarbose in long-term acarbose users.